Tinjauan Kepatuhan Kewajiban Pajak Penghasilan UMKM Kuliner Malam di Wilayah KPP Pratama Madiun - Salsabela Sakina Sukma; Antonius Ragil Kuncoro (JURNAL PAJAK INDONESIA, 2022)
This study aims to review and observe the income tax compliance of night culinary Micro, Small, and, Medium Enterprise (MSMEs) in KPP Pratama Madiun area, including the motives behind their compliance or non-compliance and the obstacles and solutions made by KPP Pratama Madiun in terms of taxing night culinary MSMEs. This study uses a descriptive qualitative research method. The results of this study indicate that the level of compliance of night culinary MSMEs is very low, only one from eight performs the obligation to register, pay, and report tax. The motives that influence non-compliance are generally due to the lack of understanding and many entrepreneurs want to fulfill their tax obligations if there is social equality for all similar enterprises, while for obedient taxpayers it is generally due to internal motivation. In terms of the obstacles faced by KPP Pratama Madiun is the lack of awareness of entrepreneurs, therefore the tax authorities tried to approach by increasing activities in the field.